2019
DOI: 10.2139/ssrn.3464295
|View full text |Cite
|
Sign up to set email alerts
|

Tax Compliance in the Rental Housing Market: Evidence from a Field Experiment

Abstract: We study rental income tax compliance using a large-scale randomized field experiment and register data with third-party information on the ownership of apartments. We analyze the responses of potential landlords to treatment letters notifying them of stricter tax enforcement, or providing simplifying information on filing practices for the rental income tax. We find that both types of letters caused an increase in the propensity to report rental income, with letters notifying landlords of the use of third-par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
5
2
Order By: Relevance
“…For instance, simple reminders are sent to taxpayers to overcome the problem of limited attention (Hernandez et al 2017, Mascagni et al 2017. The problem of cognitive overload is usually bypassed through the simplification of the communication language, the introduction of visual stimuli or provision of information how to file the income (De Neve et al 2019, Eerola et al 2019. This sub-category of non-deterrence nudges also include communications which introduce various types of informational content, such as a sentence on tax deductible donations (Biddle et al 2018), phone number for enhanced consumer service (Coleman 1996), a statement of intent by tax administration to help during the filing process (Hasseldine et al 2007), and the like.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…For instance, simple reminders are sent to taxpayers to overcome the problem of limited attention (Hernandez et al 2017, Mascagni et al 2017. The problem of cognitive overload is usually bypassed through the simplification of the communication language, the introduction of visual stimuli or provision of information how to file the income (De Neve et al 2019, Eerola et al 2019. This sub-category of non-deterrence nudges also include communications which introduce various types of informational content, such as a sentence on tax deductible donations (Biddle et al 2018), phone number for enhanced consumer service (Coleman 1996), a statement of intent by tax administration to help during the filing process (Hasseldine et al 2007), and the like.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…For instance, simple reminders are sent to taxpayers to overcome the problem of limited attention (Hernandez et al 2017, Mascagni et al 2017. The problem of cognitive overload is usually bypassed through the simplification of the communication language, the introduction of visual stimuli or provision of information how to file the income (De Neve et al 2019, Eerola et al 2019. This sub-category of non-deterrence nudges also include communications which introduce various types of informational content, such as a sentence on tax deductible donations (Biddle et al 2018), phone number for enhanced consumer service (Coleman 1996), a statement of intent by tax administration to help during the filing process (Hasseldine et al 2007), and the like.…”
Section: Tax Compliance Measures and Types Of Nudgesmentioning
confidence: 99%
“…The results of the experiment showed that the intervention was effective. Similarly, in a controlled experiment for Finland, Eerola et al (2019) analyze the responses of potential landlords of rental housing to letters notifying them of stricter tax enforcement. The authors find letters effective, and also find positive spillover effects of tax enforcement between spouses and among landlords who did not report any rental income in the previous year.…”
Section: Introductionmentioning
confidence: 99%